Microbial carbohydrate-active enzymes influence soil carbon by regulating the of plant- and fungal-derived biomass decomposition in plateau peat wetlands under differing water conditions - Xiong, Mingyao; Jiang, Wei; Zou, Shuzhen; Kang, Di; Yan, Xianchun (Frontiers in Microbiology, 2023)
Peatlands at the eastern margin of the Tibetan Plateau are important carbon sinks and water sources in Asian terrestrial ecosystems. It is important to explore their microbial-driven water-carbon synergistic mechanisms to understand the driving mechanisms of carbon processes in peatlands. Based on macrogenomic sequencing techniques, we investigated the characterization of soil microbial carbohydrate-active enzymes (CAZymes) under different water gradients in peatland at the eastern margin of the Tibetan Plateau. According to the results, these three phyla (Chloroflexi, Gemmatimonadetes, and Verrucomicrobia) differed significantly between water gradients. Under dried wetlands, the abundance of CAZymes involved in hemicellulose and glucan degradation increased by 3.0×10-5 and 3.0×10-6, respectively. In contrast, the abundance of CAZymes involved in chitin degradation decreased by 1.1×10-5 (P < 0.05). It highlights that regulating plant- and fungus-derived carbon metabolism processes by soil microorganisms in highland peatlands is a crucial mechanism for their response to water changes. Most plant-derived carbon fractions are regulated by soil enzymes (endo-beta-1,4-xylanase, alpha-L-arabinofuranosidase, and alpha-L-fucosidase) containing CAZymes functional genes. Additional findings in this enzyme gene pathway indicate that water changes that affect soil carbon fractions indirectly influence the three enzyme gene metabolic pathways related to plant carbon sources (the glycolysis/gluconeogenesis , other glycan degradation and amino sugar, and nucleotide sugar metabolism). Overall, this study highlights the significance of microbial CAZymes in highland peatland soil carbon processes and indicates that microbial conversion of plant and fungal biomass carbon is more sensitive to water changes.